QUALITIES OF BEING THE BEST TEACHER (Proceedings of International Educators Conference, 2023)
Role of teacher is importance not only in the classroom but also in society. The teacher is responsible to obtain and give the knowledge and skills from their generation to give to the generation coming. Doing so, the teacher ensures the survival of human and its life. In fact, by their training and dedication, teacher becomes the key to quality education.